Influence of Employee Recognition on Employee Motivation and Job Satisfaction in the Nigerian Banking Industry - Ekwutosi Theresa Ezeanolue; Chinelo Patience Ohanyere; Obinna Solomon Eboh (PT. BATARI EDU CALYA, 2026)
Employee productivity in the banking industry is influenced by multiple factors, with compensation and motivation being critical determinants. Ensuring that employees are rewarded and motivated is essential for organizational performance. The study employs a case study approach to examine how incentive strategies influence employee productivity in GT Bank, Access Bank, and First Bank Nigeria Plc. Using a triangulation method, it integrates qualitative interviews and observations with quantitative questionnaires and secondary data on salaries and earnings. A stratified random sample of 300 employees was selected, representing managers, senior, and junior staff. Data were analyzed using SPSS, with descriptive and correlation statistics employed to assess relationships between compensation, motivation, and productivity. Productivity results showed moderate perceptions, with only two items rated as critical, while others were fairly or weakly significant. Job satisfaction was generally high, with strong satisfaction in working conditions, effort, relationships, and communication, though retention was weaker. Regression analysis revealed a weak relationship between monetary incentives and predictors (low R²), though ANOVA indicated statistical significance. Among variables, only employee factors significantly influenced incentives. Secondary data showed a strong positive relationship between salaries and gross earnings, with high correlation (r = 0.863) and substantial explanatory power (R² = 74.4%), confirming that monetary incentives significantly relate to productivity. Findings indicate that while compensation strongly influences productivity, motivation and job satisfaction play supportive roles. Inequities in promotion and limited non-financial incentives can reduce engagement. The study concludes that integrating fair compensation with effective motivational strategies is crucial for optimizing performance in the banking sector.